An Engineering Approach to Time-Frequency Uncertainty Criteria - Udal, A.; Kukk, V. (Elektronika ir Elektrotechnika, 2012)
The conventional formulation of the Fourier Uncertainty Principle associated with the standard deviations methodology has several drawbacks that makes this theoretical approach often useless for practical applications. Beside of that a more practical engineering approach that discusses separately the different harmonics in any time-windows and detects signal spreading in time- and frequency domains by the relative levels, may be formulated. In contrast to the single Gaussian pulse of conventional theoretical approach, the primary model task of this engineering approach is the harmonic signal in rectangular time window. The engineering approach gives possibility to formulate the simple time-frequency uncertainty product constants, for example, 1.206709 for the 50% level detection criterion in the case of rectangular time window. Ill. 6, bibl. 15, tabl. 1 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1043